PREVALENCE OF DRUG AND SUBSTANCE ABUSE AMONG UNDERGRADUATES IN THE UNIVERSITY OF LAGOS: IMPLICATION FOR CAMPUS-WIDE COUNSELLING - MODEBELU, Obiageli Josephine; ADENIYI, Emmanuel Oladipo (Ilorin Journal of Education, 2023)
The study investigated the prevalence of drug and substance abuse among undergraduates in the University of Lagos and its counselling implication. The survey design method was adopted for the study. The population of the study was all undergraduates in the 12 Faculties of the University. Three research questions and one hypothesis were raised to guide the study. The sample size was purposively selected from the population and a total of 196 female and 190 male students. A 22-item questionnaire title ‘’Drug Use and Abuse among Undergraduates Questionnaire’’ (DUAAUQ) was used for the study. To determine the internal consistency of the instrument, Cronbach alpha was used and a reliability coefficient of 0.87 was obtained. A total of 386 copies of questionnaire were administered, however only the 308 that were returned and properly filled were used for analysis. Rank order, simple percentages and mean score were used to answer the research questions while the t-test was used to test the hypothesis at 0.05 level of significance. The finding of the study revealed that the following drugs and substances alcohol, cough syrups, Indian hemp (Igbo or weed), pain killers, coffee, tobacco, kolanuts. inhalants, cocaine, cannabis were abused by the students. The study also showed that there are many reasons why the students abuse drugs, which include to stay awake to study, to fight depression and anxiety, influence from peers and acquaintances, to win in sports, among others. The study also showed that the students understand the dangers of drug and substance abuse. The study found out that there was significant difference based on gender (tcal -3.493, P = 0.05) in drug and substance abuse among the students. Based on the findings of the study, it was recommended that drug education should be incorporated into the curriculum of the University and that alcohol and other substances should be prohibited on campus.